New insight into contradictive relationship between sensitivity and working bandwidth of cilium MEMS bionic vector hydrophone. (23rd September 2019) - Xu, Qingda; Zhang, Guojun; Zhao, Yujie; Wang, Renxin; Ding, Junwen; Zhang, Xiaoyong; Xue, Chenyang; Zhang, Wendong
Abstract: Sensitivity and working bandwidth are two important features of cilium MEMS bionic vector hydrophone. However, in previous studies, they were mutually inhibited so that they could not be optimized simultaneously, which means that the method of increasing sensitivity would reduce the working bandwidth. This paper presents an efficient solution to this contradictive relationship. First of all, this paper makes a theoretical analysis of device structure through the two-degree of freedom mechanics system instead of previous single degree of freedom. Then, theoretical analysis, theoretical simplified model simulation analysis and actual model simulation analysis are performed by mathematical modeling and ANSYS 17.0 software. Moreover, four hydrophones of different cilium diameters are fabricated and comparison calibration test is performed. The results demonstrate that the sensitivity and working bandwidth can be increased simultaneously. Besides, their concave points of directivity curves are almost equal to each other. Finally, the sensitivity of the optimal structure can reach up to  −185.9dB (1250 Hz 0 dB at 1 V µ Pa −1 ) and its working bandwidth is in the range of 20–1250 Hz which is the widest among all previous optimized structures.